Epileptic seizure-induced cardiac injury as a cause of sudden unexpected death in epilepsy: Evidence from pathological analyses - Tao Song; Shisheng Zhu; Jianbo Li (Wolters Kluwer Medknow Publications, 2018)
Sudden unexpected death in epilepsy (SUDEP) is the most frequent cause of death in people with epilepsy. The detailed mechanisms of SUDEP have not been elucidated. Moreover, it is still difficult for clinicians to predict and prevent the occurrence of sudden death in patients with epilepsy. Seizure-related cardiac complications were considered to play a significant role in the physiological changes that lead to SUDEP. This report described a case of sudden death of an 11-year-old boy with epilepsy. Detailed autopsy and pathological analyses were performed to determine the cause of death. Seizure-induced myocardial fibrosis was observed and deemed to be the cause of SUDEP. This study clearly showed the importance of improving the protection of cardiac function in the reductions of sudden deaths among patients with epilepsy. In addition, further studies in the pathophysiology of patients with epilepsy may help in improving our understanding of the mechanisms of SUDEP and adding new insight into the development of seizure-induced cardiovascular and respiratory changes that may contribute to sudden death in epileptics.